Historical Slave Trade and Corporate Tax Evasion in Africa - Niu, Geng (Journal of business ethics, 2026)
We examine the impact of the African slave trade on corporate tax evasion in modern Africa. Using data from 28 African countries, we document that firms are more likely to evade taxes in countries that suffered a higher level of historical slave extraction. This finding is robust to an instrumental variable analysis. We further use household survey data to show that the slave trade has a long-lasting negative impact on tax compliance attitudes in the society and the quality of tax enforcement institutions. Our results highlight and quantify a pronounced historical determinant of cross-country differences in corporate decisions.